2013
DOI: 10.1016/j.jacc.2012.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Left Atrial Appendage Suture Ligation Using the LARIAT Device in Patients With Atrial Fibrillation

Abstract: LAA closure with the LARIAT device can be performed effectively with acceptably low access complications and periprocedural adverse events in this observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
294
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(304 citation statements)
references
References 55 publications
5
294
0
5
Order By: Relevance
“…1320 The results from the multicenter registry demonstrated a high acute closure rate, but procedural success was limited by bleeding. 1321 More recent results showed that LARIAT device implantation was associated with a lower rate of leaks at 1 year of follow-up and a 1.1% rate of TIA or stroke.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…1320 The results from the multicenter registry demonstrated a high acute closure rate, but procedural success was limited by bleeding. 1321 More recent results showed that LARIAT device implantation was associated with a lower rate of leaks at 1 year of follow-up and a 1.1% rate of TIA or stroke.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…Long-term follow-up revealed severe pericarditis, late stroke, and sudden death in two patients each and late pericardial effusion in one patient. 106 …”
Section: Lariat Techniquementioning
confidence: 99%
“…This type of complication is not reported in previous larger series on percutaneous ligation of the LAA utilizing the same device. [6][7][8] The most common intraoperative complication seen in other series and case reports is right ventricular perforation during epicardial access or perforation of the LAA itself. [6][7][8][9] Three other cases at our institution were performed without complication by the same operators using an identical technique.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies into the delivery design and technique of percutaneous LAA ligation are warranted, and increased experience with this device has already extended beyond the 137 cases referred to in this report. [6][7][8] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation